Spontaneous Remission After a Hypercalcemic Crisis Caused by an Intracystic Hemorrhage of Bilateral Parathyroid Adenomas: A Case Report and Literature Review - Liu, Yaoxia; Li, Jianwei; Liu, Hui; Yang, Han; Qiao, Jingtao; Wei, Tao; Wang, Tao; Yu, Yerong (Frontiers in Endocrinology, 2021)
Background: Hyperparathyroidism is a common cause of hypercalcemia; however, spontaneous remission after a hypercalcemic crisis caused by an intracystic hemorrhage of parathyroid adenomas is very rare. The question, then, is “What is the best choice in such cases--conservative treatment or surgery?” Method: A 47-year-old male patient with primary hyperparathyroidism and a hypercalcemic crisis is reported. Hypercalcemia was spontaneously relieved thereafter. The post-operative pathology results indicated an intracystic hemorrhage of bilateral parathyroid adenomas. Results: After the case report, a literature review is also included to summarize the clinical features of this patient and to provide special reference for clinical diagnosis and treatment of similar cases. Conclusions: The choice of surgical timing for such cases can be made based on the comprehensive consideration of clinical symptoms and changes in parathyroid function.